Preparation method of bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film
By combining kelp polysaccharides, citrus polyphenols, and moringa leaf extract with zein/hyaluronic acid, a biodegradable preservation film with antibacterial and antioxidant properties was prepared, solving the environmental pollution problem caused by traditional synthetic materials and improving the mechanical properties and preservation effect of the film.
Patent Information
- Application Number
- CN202510960354.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-11-07
AI Technical Summary
Traditional synthetic food packaging materials cause serious environmental pollution, and there is a lack of renewable and environmentally friendly bio-based protein membrane materials.
A biodegradable preservative film with antibacterial and antioxidant properties was prepared by combining kelp polysaccharides, citrus polyphenols, and moringa leaf extract with zein/hyaluronic acid and using eutectic solvent extraction and carbon dioxide expanded ethanol extraction techniques.
It improves the mechanical properties and preservation effect of the membrane, extends the shelf life of food, reduces microbial contamination, and achieves environmentally friendly biodegradability.
Smart Images

Figure CN120904492A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of food, and particularly relates to preparation and application of a zein / hyaluronic acid antibacterial and antioxidant degradable preservative film containing sea tangle polysaccharide, citrus polyphenol and moringa oleifera leaf extract. BACKGROUND
[0002] With the global population growth and economic development, the demand for food packaging materials and biomedical materials is increasing. Traditional synthetic materials mainly rely on non-renewable resources such as petroleum, and their production and waste disposal processes have caused serious pollution to the environment. Therefore, finding renewable and environmentally friendly green materials has become a research hotspot. Bio-based protein films are considered as an ideal substitute for traditional synthetic materials as a kind of degradable biomaterials with good biocompatibility and sustainability. Bio-based protein films have natural biocompatibility and degradability, as well as good mechanical properties and functionality, which can make up for the shortcomings of traditional synthetic materials. Proteins are the basic components of living organisms, and have good biocompatibility, degradability and multifunctionality. Protein films can be formed by self-assembly and cross-linking of proteins, and have porous structure and good permeability, which are suitable for various application fields. Developing more bio-based protein films is of great significance for food packaging and biomedical materials.
[0003] 1. Zein
[0004] Zein has unique film-forming properties. Zein is rich in sulfur-containing amino acids, and the protein molecules are connected by strong disulfide bonds, hydrophobic bonds, which is the basis for zein to easily form a film. When the film-forming liquid is coated, with the evaporation of the solvent, the film dehydrates and dries, increasing the protein concentration in the film-forming liquid. When the concentration exceeds a certain value, the protein condenses, and intermolecular hydrogen bonds, disulfide bonds and hydrophobic bonds are formed to maintain the network structure of the film, forming a transparent and glossy zein film. Zein has antioxidant properties. Adding ester compounds to zein can improve its tensile strength and reduce its permeability. Antibacterial agents can also be added to inhibit the growth of pathogenic microorganisms.
[0005] 2. Properties of hyaluronic acid
[0006] Hyaluronic acid (HA) is a natural mucopolysaccharide, which is a white macromolecular substance, colorless and odorless, with good water solubility and water absorption, and is not easily dissolved in organic solvents. The hyaluronic acid used in the market at present is mainly sodium salt, that is, sodium hyaluronate, which is a white powdery or fibrous solid substance. The most outstanding physical and chemical properties of HA are its viscoelasticity and non-Newtonian rheology. The content and molecular weight of HA are important factors affecting the viscosity of the system. Under certain conditions, the viscosity of the solution increases with the increase of the concentration, and the viscosity increases with the increase of the molecular weight, which is mainly because the HA molecules will intertwine with each other, thereby changing the viscosity of the system. The rheological properties of HA are non-Newtonian fluid, and its viscosity decreases with the increase of shear rate. This is because the faster the shear rate, the greater the shear force; the greater the shear force, the greater the stretching or deformation of HA molecules. The physical properties of HA, such as spatial configuration, shape, and rheology, are also strongly related to the concentration of salt, pH, and temperature in the HA system.
[0007] 3. Laminarin
[0008] Laminaria is a large economic brown algae with both edible and medicinal health functions, and its polysaccharides have significant functions of regulating immunity, anti-virus, anti-tumor, anti-coagulation, and anti-oxidation.
[0009] Laminarin not only has good antioxidant properties and bacteriostatic effects, but also has certain inhibitory effects on Escherichia coli, Salmonella, Staphylococcus aureus, and Enterococcus faecalis, and the diameter of the inhibition zone increases with the increase of the mass concentration of polysaccharides.
[0010] In addition, laminarin also has the function of reducing irradiation. By treating fresh pork with laminarin and electron beam irradiation, the rising trend of pork pH value is slowed down, the hardness and chewiness of pork are reduced, the rate of fat oxidation is significantly slowed down, and certain bacteriostatic effect is maintained, greatly extending the shelf life of pork.
[0011] 4. Citrus polyphenol
[0012] Citrus fruits contain a large amount of polyphenolic substances, which have good antioxidant and bacteriostatic effects. Citrus polyphenol is a natural fruit extract of citrus fruits such as red oranges, grapefruits, and oranges, which is prepared by a unique extraction technology and contains more than 60% polyphenolic substances, including flavonones, polymethoxy flavone glycosides, and phenolic acids.
[0013] (1) Antioxidant effect
[0014] Citrus fruit polyphenols have strong antioxidant capacity and can directly scavenge active oxygen and destroy the corresponding free radical chain reaction. The phenolic hydroxyl groups contained in polyphenols generally have reducing properties and often act as hydrogen donors by regenerating other antioxidants or chelating with variable metal ions (Cu2+ Fe 2+ )Chelate and other ways of action, can directly or indirectly inhibit lipid peroxidation, is a natural lipid protectant.
[0015] (2) Bacteriostatic effect
[0016] Flavonoids, limonin and other substances contained in the crude extract of citrus peel have good bacteriostatic effect. The bacteriostatic effect of products obtained by different extraction agents of citrus peel is significantly different, and the antibacterial activity of methanol extract is stronger than that of other reagent extracts. The effective antibacterial active ingredients of citrus peel mainly include flavonoids, saponins, essential oils, alkaloids and other substances, hesperidin and D-limonene have broad-spectrum bacteriostatic effect on common fruit and vegetable contaminating bacteria. Naringin, hesperidin, polymethoxyl flavones, honey orange flavones and citrus flavones in grapefruit and orange can effectively inhibit the growth of penicillium digitatum, and polymethoxyl flavones have more obvious effect than hydroxyl flavones. In addition, hesperidin can also effectively inhibit the growth of escherichia coli, enterobacter cloacae, salmonella typhi, staphylococcus aureus and other bacteria, and 4'-hydroxy-3-methoxy flavone can effectively prevent and control antirhinovirus and poliovirus.
[0017] 5. Moringa oleifera Lam. leaf extract
[0018] Moringa oleifera Lam. is a perennial tropical deciduous tree of the Moringaceae family, originally from India, widely planted in the tropics and subtropics of Asia and Africa, and also introduced and cultivated in Guangdong, Guangxi, Yunnan, Fujian and Taiwan of China. As a new resource food, Moringa oleifera Lam. has the advantages of strong environmental adaptability, rapid growth, rich and comprehensive nutrition, multiple biological activities, and has a long history of application in traditional Indian medicine, with potential development prospects.
[0019] Moringa oleifera Lam. leaves contain flavonoids, which can release hydrogen atoms from hydroxyl groups. The hydroxyl groups connected to free radicals act as antioxidants, neutralizing and stabilizing free radicals and preventing chain reactions, thereby preventing potential damage to lipids, proteins or DNA, and providing antioxidant properties to the film. Moringa oleifera Lam. leaf extract can reduce food oxidation and scavenge free radicals, and the antioxidant activity of the edible film will increase with the increase of the concentration of Moringa oleifera Lam. leaf extract.
[0020] Recent studies have also found that Moringa oleifera Lam. leaf extract has antibacterial effect. In vitro antibacterial method research results show that 5mg / mL concentration of Moringa oleifera Lam. leaf acetone extract has antibacterial activity against escherichia coli, staphylococcus aureus, proteus vulgaris, enterobacter cloacae and micrococcus kristinae, but has no antibacterial effect on pseudomonas aeruginosa, bacillus, klebsiella pneumoniae, bacillus cereus and streptococcus faecalis; 5mg / mL concentration of Moringa oleifera Lam. leaf water extract and acetone extract also have no antibacterial activity against candida albicans and aspergillus flavus.
[0021] Moringa oleifera leaf extract is rich in natural macromolecular substances such as cellulose, polysaccharide and protein. When it is added to the film forming system, it can significantly improve the mechanical properties of the film such as tensile strength and elongation at break as a reinforcing phase, making the film more tough and durable. The polysaccharide in it has good hydrophilicity, which can effectively regulate the air permeability and moisture permeability of the film, so as to accurately control the transmission amount of gas and moisture in packaging. The rich flavonoids and polyphenols in Moringa oleifera leaf extract endow the film with excellent antioxidant properties. When used in food packaging film, it can effectively delay the oxidation and deterioration of food and prolong the shelf life. The natural antibacterial ingredients (such as isothiocyanate) in the extract can inhibit the growth and reproduction of common food spoilage bacteria and pathogenic microorganisms, endowing the film with antibacterial activity and playing an active role in preservation, reducing the loss caused by microbial contamination during storage and transportation. At the same time, Moringa oleifera leaf extract is derived from natural plants, which can enhance the biocompatibility and degradability of the film, facilitate the rapid decomposition of the film in the natural environment after being discarded, reduce environmental pollution, and has great application potential in the field of degradable packaging film and agricultural covering film.
[0022] The above material has no related reports in the field of biobased protein degradable film. SUMMARY
[0023] The purpose of the present application is to provide a preparation method of a zein / hyaluronic acid degradable film containing seaweed polysaccharide, citrus polyphenol or Moringa oleifera leaf extract.
[0024] The preparation method of the antibacterial and antioxidant zein / hyaluronic acid degradable preservative film of the present application is as follows:
[0025] (1) After dissolving hyaluronic acid completely in ethanol, zein is added and stirred and dissolved to obtain a zein-hyaluronic acid solution;
[0026] (2) Dissolve the citrus polyphenol extract into the zein-hyaluronic acid solution, and under stirring, add the zein-hyaluronic acid-citrus polyphenol solution into distilled water, and perform rotary evaporation in a water bath to remove ethanol;
[0027] (3) Mix the seaweed polysaccharide solution with the zein-hyaluronic acid-citrus polyphenol solution after removing ethanol to obtain a mixed solution; add glycerol, gelatin and agar to the mixed solution, stir and mix under water bath condition, remove bubbles, film-forming, dry to obtain a zein / hyaluronic acid degradable preservative film containing seaweed polysaccharide and citrus polyphenol.
[0028] Further, the mass ratio of zein to hyaluronic acid in step (1) is 5-10:1.
[0029] Further, the mass concentration of the kelp polysaccharide solution and the citrus polyphenol solution in step (2) is 0.75-1.25% and 2.5-5%, respectively.
[0030] Further, after the removal of ethanol in step (2), the content of the zein in the mixed solution is 0.2-2%.
[0031] Further, the kelp polysaccharide extraction method is as follows:
[0032] After the kelp powder is uniformly mixed with the eutectic solvent in a water bath, microwave extraction is performed, the extraction solution is centrifuged, the supernatant is collected, repeated centrifugation is performed, the supernatant is collected three times, the last collected supernatant is added with 95% ethanol, mixed, alcohol precipitation is performed, centrifugation is performed, the grayish white precipitate is collected, ethanol is volatilized, and freeze-drying is performed to obtain kelp polysaccharide in the form of loose and porous, without obvious clumping or collapse.
[0033] The eutectic solvent is a mixture of choline chloride and lactic acid, a mixture of choline chloride and citric acid, a mixture of betaine and lactic acid, or a mixture of betaine and urea.
[0034] Further, the citrus polyphenol extraction method is as follows:
[0035] The citrus dry powder is added with a solvent for dissolution, mixed, ultrasonic extraction is performed, centrifugation is performed, and the supernatant is collected to obtain the citrus polyphenol.
[0036] The solvent is prepared from choline chloride and glucose at a mass ratio of 1:0.5-2.
[0037] A preparation method of the corn protein zein / hyaluronic acid degradable preservative film with antibacterial and antioxidant properties is as follows:
[0038] (1) After hyaluronic acid is completely dissolved in ethanol, zein is added, stirred and dissolved to obtain a zein-hyaluronic acid solution;
[0039] (2) The moringa leaf extract is dissolved into the zein-hyaluronic acid solution, and the zein-hyaluronic acid-moringa leaf extract solution is added into distilled water under stirring, and rotary evaporation is performed in a water bath to remove ethanol;
[0040] (3) The kelp polysaccharide solution is taken, added into the zein-hyaluronic acid-moringa leaf extract solution from which ethanol has been removed, stirred, and then stirred after the addition of sodium alginate solution, glycerol and sorbitol to obtain a polysaccharide solution; Tween-80 is added dropwise, and homogenization is performed to obtain an emulsion; defoaming treatment is performed;
[0041] (4) The emulsion after defoaming in step (3) is poured into a film, dried, and the corn protein-HA film of kelp polysaccharide and moringa leaf extract is obtained.
[0042] Further, the mass concentration of the laminarin solution and the moringa leaf extract in step (2) is 0.75-1.25% and 2.0-3.0%, respectively.
[0043] Further, the mass concentration of the sodium alginate solution in step (3) is 0.1%; the volume-mass ratio of the corn alcohol-soluble protein-hyaluronic acid-moringa leaf extract solution, the sodium alginate solution, the glycerol and the sorbitol after removing the ethanol is 50-150 mL: 50-150 mL: 2-3 mL: 1 g.
[0044] Further, the corn alcohol-soluble protein-hyaluronic acid-moringa leaf extract solution in step (2) is added into distilled water, and the dropping speed is 4-6 mL / min.
[0045] Further, the moringa leaf powder is extracted by carbon dioxide-expanded ethanol supercritical fluid, collected, and placed in an ice bath in the dark to obtain the moringa leaf extract; the solvent is carbon dioxide with a purity of ≥99.9% and ethanol with a concentration of 60%.
[0046] The present application comprises the following beneficial effects:
[0047] The bio-based edible packaging material corn alcohol-soluble protein has unique film-forming property, and the hyaluronic acid has important functions such as water retention, antibacterial property, free radical scavenging and film-forming property. The deep eutectic solvent is a green solvent, which is safe as an extractant and can also improve the performance of the film. The laminarin extracted by the deep eutectic solvent, the citrus polyphenol and the moringa leaf extract extracted by carbon dioxide-expanded ethanol have antioxidant effect and antibacterial effect. The synergistic effect between the substances can effectively improve the preservation effect of the composite film, and the release property of the composite film can further improve the preservation effect of the fresh-cut aquatic products. BRIEF DESCRIPTION OF DRAWINGS
[0048] Figure 1 It is a protein / polymer antibacterial and antioxidant degradable film containing laminarin, citrus polyphenol or moringa leaf extract; A is a corn alcohol-soluble protein-HA film containing laminarin and citrus polyphenol, and B is a corn alcohol-soluble protein-HA film containing laminarin and moringa leaf extract.
[0049] Figure 2 It is a water vapor transmission rate diagram of the protein-HA film of the present application.
[0050] Figure 3 It is a tensile strength diagram of the protein-HA film of the present application.
[0051] Figure 4 It is a bacteriostatic diagram of the protein-HA film of the present application.
[0052] Figure 5 Figure for antioxidation activity of protein-HA film of the present application;
[0053] Figure 6 Figure for volatile basic nitrogen of protein-HA film of the present application;
[0054] Figure 7 Figure for thiobarbituric acid value of protein-HA film of the present application;
[0055] Figure 8 Figure for fish tissue slice photos preserved by protein-HA film of the present application; A is fresh fish sample; B is fish sample stored for 10 days in the control group; C is fish sample stored for 20 days in the control group; D is fish sample stored for 10 days by laminarin-citrus polyphenol-protein polysaccharide film; E is fish sample stored for 20 days by laminarin-citrus polyphenol-protein polysaccharide film; F is fish sample stored for 10 days by laminarin-moringa leaf extract-protein polysaccharide film; G is fish sample stored for 20 days by laminarin-moringa leaf extract-protein polysaccharide film. DETAILED DESCRIPTION
[0056] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the following will describe the spirit of the present application in detail. Any person skilled in the art can make changes and modifications to the technology taught by the present application content without departing from the spirit and scope of the present application content.
[0057] The schematic embodiments of the present application and the descriptions thereof are used to explain the present application, but are not as limitations to the present application.
[0058] Embodiment 1
[0059] 1. Extraction of laminarin by low-temperature eutectic method in cooperation with microwave method
[0060] 1.1 Preparation of low-eutectic solvent
[0061] Four kinds of deep eutectic solvents (DES1 to DES4) were prepared as shown in Table 1. The hydrogen bond acceptors (choline chloride, betaine) and hydrogen bond donors (lactic acid, citric acid, urea) were mixed in a certain molar ratio in a beaker, and then the beaker was placed on a heat collecting constant temperature heating magnetic stirrer at a temperature of 75-85°C, and stirred magnetically for 2-4 h until the reagents were uniform and transparent. After the reaction was completed, it was taken out and cooled to room temperature to obtain a colorless transparent liquid, which remained uniform and transparent after being placed at room temperature for one week. The solvent generally has high viscosity, which is not conducive to the dissolution and mass transfer of polysaccharides, and brings difficulties to extraction and separation, so 20% distilled water was added during synthesis (20% distilled water was added, although water participated in the solvation structure, but the main components of DES (such as choline chloride, urea, etc.) usually still dominated. This enables the system to obtain good fluidity while maximizing the retention of the core solvent properties and functions of DES, allowing it to participate in the formation of the DES hydrogen bond network as structural water rather than dilute water, accelerating the formation of the DES eutectic solution, and improving the stability of the DES), which can reduce the viscosity of the system while accelerating the synthesis speed. After synthesis, it was stored at room temperature, and the storage time was generally not more than one week. The different types of DESs used in this example are shown in Table 1.
[0062] Table 1: DESs used in the synthesis
[0063]
[0064] 1.2 Deep eutectic solvent assisted microwave extraction of polysaccharides from kelp
[0065] Accurately weigh 0.5 g of kelp powder (accurate to 0.0001 g) and place it in a sample cup, add 15 mL of the pre-prepared deep eutectic solvent shown in Table 1, and place it in a 60°C constant temperature water bath, stir evenly, and allow the powder to fully contact and swell with the solvent before starting the polysaccharide extraction.
[0066] During the microwave extraction process, first perform the main control tank installation operation and the standard tank installation operation, place the assembled tank body tube rack on the turntable in turn, and try to distribute the tank bodies evenly on the turntable. Select the program and set the required procedure (microwave power 400 W, microwave temperature 60°C, microwave time 60 min), after the microwave assisted extraction is completed, transfer the extract to a 50 mL centrifuge tube, then place it in a 4000 r / min high speed table centrifuge, centrifuge for 5 min, collect the supernatant, repeat the operation three times, and place the collected supernatant in a sample bottle.
[0067] To the sample bottle containing supernatant, 3 volumes of 95% ethanol (final concentration about 70%~80%) were slowly added while stirring until mixed evenly, sealed and placed in the 4°C refrigerator for alcohol precipitation for 12~24 h until the polysaccharide was fully precipitated. The alcohol precipitation liquid was loaded into a 50 mL centrifuge tube, and centrifuged at 5000 r / min in a high-speed table centrifuge for 15 min, and the precipitate was collected. The precipitate was placed in a frozen sample tray, and after the ethanol was completely volatilized, it was placed in a ultra-low temperature refrigerator at -60°C for pre-freezing, and then placed in a freeze dryer with a temperature of -50°C, a vacuum degree of 0.1 Pa, and a time of 24 h. The freeze-dried rough kelp polysaccharide was in a loose porous state without obvious clumping or collapse.
[0068] 2. Preparation of citrus polyphenols
[0069] Preparation of citrus dry powder: Citrus peels were placed in a tray oven and dried at 32°C for 24 h, and the moisture content after drying was less than 15%. A universal grinder was used to grind the dried peels to obtain uniform powder. The powder was sieved to obtain a particle size of ≤500 μm. The sieved powder was stored at room temperature in a resealable bag lined with aluminum foil.
[0070] Preparation of eutectic solvent: Choline chloride and glucose were mixed in a molar ratio (ChCl:Glu=1:0.5 mol / mol), with ChCl as the hydrogen bond acceptor (HBA) and Glu as the hydrogen bond donor (HBD). The mixture was heated to 90°C in a water bath and continuously stirred for 90 min until a clear liquid phase was obtained. Deionized water was added to the prepared NADES at a ratio of 60%, and mixed well.
[0071] Citrus polyphenol extraction process: 1 g of citrus dry powder was dissolved in 10 mL of eutectic solvent (choline chloride:glucose=1:0.5~2 with water to make a eutectic solvent with a mass percentage of 60%), and mixed evenly using a vortex mixer. Then, ultrasonic extraction was carried out at an ultrasonic frequency of 42 kHz, an extraction time of 30 min, and a temperature of 60°C. Finally, the extraction mixture was separated by centrifugation at 5000 rpm, 4°C for 20 min, and the supernatant was the citrus polyphenol extract.
[0072] 3. Preparation of Moringa oleifera leaf extract
[0073] Moringa oleifera leaf extract extraction method: Moringa oleifera leaf extract is extracted by carbon dioxide expansion ethanol (CO2-expanded ethanol, CXE). In a supercritical fluid extraction system, the material in the extraction kettle is dried to a constant weight, and the Moringa oleifera leaf sample powder is mixed with an equal amount of glass beads. Carbon dioxide with a purity of ≥99.9% is pressurized by a plug pump at a flow rate of 0.3 L / min, and ethanol with a concentration of 60% (w / w) is pumped into the mixer at a flow rate of 1.2 mL / min. The two are mixed in the mixer to form a subcritical CXE fluid and enter the extraction kettle. The material is extracted at 50°C and 7 MPa for 160 min. During dynamic extraction, the extract is collected in a 100 mL collection bottle and stored in an ice bath in the dark.
[0074] 4. Preparation of HA-Zein film added with laminarin and citrus polyphenol
[0075] Preparation of Zein-HA complex solution:
[0076] (1) Zein-HA complex solution was prepared by anti-solvent co-precipitation method. 0.1 g of hyaluronic acid was added to 100 mL of 75% ethanol solution. Ultrasonic for 30 min to completely dissolve (temperature 40°C, 45 KHz, ultrasonic power 200 W). Take 1.0 g of Zein and add it to the above hyaluronic acid solution, stir at 1000 r / min for 10 min until completely dissolved, to obtain Zein-HA mixed solution.
[0077] After dissolving 5% citrus polyphenol extract into the above Zein-HA mixed solution.
[0078] (2) Under the magnetic stirring at 1000 r / min, the prepared 100 mL of protein-polymer-citrus polyphenol complex solution was slowly injected into 300 mL of distilled water with a syringe, and the stirring was slowly increased. In a water bath at 60°C, the rotary evaporator (-0.1 MPa) was used to remove 75% ethanol from the solution, so that the final mixed solution contained 1% Zein.
[0079] Addition of laminarin and other substances: Add laminarin to the above mixed solution, the amount of which is 0.75%~1.25%, and stir at 50°C and 1000 rpm for 5 min until completely mixed.
[0080] Slowly add 10% glycerol, 0.5% gelatin, and 0.1% agar at a uniform speed of 1000 rpm under stirring at 40°C, and mix thoroughly for 10 min. Under the conditions of 25°C and 0.098 MPa, the film solution is vacuum degassed for 0.5 h to remove bubbles, and the mixed solution is poured into a suitable container for standby.
[0081] Film formation: using a scraper vacuum suction coating machine mechanism, a size of 45 mm x 105 mm polytetrafluoroethylene plate is fixed to the coating machine, the position of the coating head is adjusted, and the coating thickness and the scraper gap. Then the cooled mixed solution is injected into the liquid supply system of the coating machine, the coating machine scraper gap is set to 1.1-1.5 mm, the coating speed is 1-5 mm / s, the heating temperature is 20-100℃, and the vacuum degree is 60-70 kPa. After coating, a 200 μm thin film uniformly coated on the polytetrafluoroethylene plate is obtained, the thin film is placed in a drying oven at 40℃ for 2 h, and the thin film is peeled off from the polytetrafluoroethylene plate to obtain a Zein-HA film of laminarin and citrus polyphenol (see Figure 1 A).
[0082] Example 2
[0083] Preparation of HA-Zein film added with laminarin and moringa leaf extract polyphenol
[0084] Zein-hyaluronic acid complex solution preparation:
[0085] (1) The Zein-HA mixed solution is prepared according to the anti-solvent co-precipitation method of step (1) of Example 1.
[0086] After dissolving 2% of the moringa leaf extract into the above Zein-HA mixed solution.
[0087] (2) Under the magnetic stirring of 1000 r / min, the prepared 100 mL of protein-polymer-moringa leaf extract complex solution is slowly injected into 300 mL of distilled water with a syringe, and the stirring is slowly added. In a water bath at 60℃, a rotary evaporator (-0.1 MPa) is used to remove 75% ethanol from the solution, so that the content of zein protein in the final mixed solution is 1%.
[0088] Addition of laminarin and other substances: add laminarin to the above mixed solution, the addition amount is 0.75%-1.25%, and mix completely under the condition of 50℃, 1000 rpm stirring for 5 min.
[0089] Slowly add 2% glycerol, 0.1% sodium alginate solution, 1% sorbitol, and 400 rpm stirring for 10 min under the condition of 50℃, uniform speed 1000 rpm stirring. Add 2 drops of Tween 80 dropwise, immediately start the high shear homogenizer (10000 r / min, 3 min), form a stable emulsion. The emulsion is transferred to an ultrasonic processor (500 W, 10 min) to eliminate internal bubbles, and an ice water bath (0-4℃) is maintained during the process to prevent temperature rise.
[0090] Casting and drying: The emulsion was poured into a 28 cm x 28 cm mold and spread evenly to a thickness of 0.15 mm with a stainless steel spatula. The mold was placed horizontally on a water platform to avoid tilting. The constant temperature incubator was set to 40°C and the humidity was 20-30% RH. The drying time was 72 h, and the mold was rotated 180° every 24 h to ensure uniform drying. After drying, the film was placed in a 75% RH environment (25°C) for 24 h to obtain the zeaxanthin-HA film. Figure 1 B).
[0091] Example 3
[0092] Performance of corn protein-HA films with laminarin and citrus polyphenols, and corn protein-HA films with laminarin and moringa leaf extract
[0093] The water vapor permeability and tensile strength of corn protein-HA films with laminarin and citrus polyphenols, and corn protein-HA films with laminarin and moringa leaf extract were studied, as well as the antibacterial properties and antioxidant activity of the films.
[0094] 1. Water vapor permeability determination: The film was covered on the mouth of an Erlenmeyer flask containing anhydrous calcium chloride, and the mouth was sealed with paraffin. The effective diameter was 20 mm, and the film was weighed and placed in an environment with a relative humidity of 90% and a temperature of 25°C. After 24 h, the mass of the Erlenmeyer flask was measured. Each sample was tested in triplicate, and the results were averaged.
[0095] WVP =△mL / tAΔP
[0096] WVP is the water vapor permeability, g·mm / m 2 ·d·kPa;△m is the water vapor migration amount, g; L is the thickness of the film, mm; t represents the test time, d; A represents the test area of the film, m 2 ;ΔP is the water vapor pressure difference between the two sides of the film, kPa.
[0097] 2. Tensile strength determination: The mechanical properties of the film sample were determined using a texture analyzer. The A / TG probe was used, with an effective tensile length of 30 mm and a test rate of 1.0 mm / s. Each sample was tested in triplicate, and the test data were expressed as: mean ± standard deviation.
[0098] Tensile strength (TS) = F / S
[0099] F represents the maximum tensile force (N) when the sample breaks; S represents the cross-sectional area (m 2 ) of the sample.
[0100] 3. Bacteriostatic property determination: The bacteriostatic property of the film was determined by agar diffusion method. The film was cut into small round pieces with a diameter of 10.00 mm by a puncher, and was pasted on the surface of agar medium uniformly coated with bacterial suspension of the test strain under sterile environment. The medium was cultured upside down, and the culture conditions of Staphylococcus aureus and Escherichia coli were 37°C for 24 h continuously. The size of the bacteriostatic ring was recorded.
[0101] 4. Antioxidant activity determination:
[0102] ①DPPH free radical scavenging rate determination: A certain amount of film sample was dissolved and soaked for 24 h to obtain the soaking solution of the compounded film. 2 mL of the soaking solution of the compounded film and 2 mL of 1 mM ethanol DPPH solution were accurately measured, mixed thoroughly, and then placed at room temperature for 30 min in the dark. The absorbance of the mixed solution was measured at 517 nm, and the control was the absorbance of ethanol at 517 nm. All test samples were tested in triplicate. The DPPH free radical scavenging rate of the sample was as follows:
[0103] DPPH free radical scavenging rate (%) = (1 - A0 / A DPPH ) × 100%
[0104] A0——the absorbance of the sample solution at 517 nm;
[0105] A DPPH ——the absorbance of the DPPH ethanol solution at 517 nm.
[0106] ②ABTS free radical scavenging rate determination: 7 mmol / L ABTS solution and 1.4 mmol / L K2S2O8 solution were prepared, and the ABTS stock solution was mixed with an equal volume of reagent and then placed in a dark environment at 4°C for 24 h. Subsequently, gradient dilution was performed with phosphate buffer at pH 7.4 until the absorbance value at 734 nm reached 0.70, thereby preparing the standard ABTS working solution.
[0107] 1.5 mL of the soaking solution of the compounded film and the ABTS working solution were accurately measured, mixed thoroughly, and then reacted for 30 min at 25°C in the dark. The absorbance of the sample at 734 nm was As; 1.5 mL of deionized water was used instead of the soaking solution of the compounded film, and the same treatment was performed to determine the absorbance value Ac as the control experiment; before determination, 1.5 mL of phosphate buffer and 1.5 mL of deionized water were mixed to perform zero adjustment. The calculation formula of the ABTS free radical scavenging rate was as follows:
[0108] ABTS free radical scavenging rate (%) = (Ac - As) / Ac × 100%.
[0109] The test results are as follows:
[0110] 1) Water vapor transmission rate
[0111] Researchers have used glucose to perform wet glycosylation modification of zein. After modification, the water vapor permeability of the zein membrane reached a stable value of 0.789 g·mm / (m). 2 ·d·kPa).
[0112] Researchers studied a zein-to-glucose ratio of 5:1 (g / g), a modification temperature of 80 ℃, and a modification time of 9 min. Under these conditions, the water vapor permeability of the zein membrane was (0.54 ± 0.33) g·mm / m. 2 ·d·kPa.
[0113] like Figure 2 As shown, the water vapor transmission rates of the HA-zein membranes containing kelp polysaccharides and citrus polyphenols, and the HA-zein membranes containing kelp polysaccharides and moringa leaf extract prepared in this experiment were 0.48 g·mm / (m). 2 ·d·kPa), 0.45 g·mm / (m 2 The water vapor permeability (·d·kPa) is significantly better than that of the membranes mentioned above.
[0114] 2) Tensile strength
[0115] Researchers have prepared a zein / curcumin / kojic acid composite film with a maximum tensile strength of 25.56 MPa; and a zein / eugenol / IRMOF-3 composite antibacterial film with a maximum tensile strength of 11.82 ± 0.23 MPa.
[0116] like Figure 3 As shown, the maximum tensile strengths of the HA-zein membranes of kelp polysaccharide and citrus polyphenols and the HA-zein membranes of kelp polysaccharide and moringa leaf extract prepared in this experiment were 25.8 MPa and 29.4 MPa, respectively, which were significantly better than the tensile strengths of the above membranes.
[0117] 3) Antibacterial properties
[0118] Researchers have prepared a zein / eugenol / IRMOF-3 composite antibacterial film with inhibition zones of up to (11.24 ± 0.37) mm and (11.82 ± 0.32) mm against Staphylococcus aureus and Escherichia coli, respectively.
[0119] With 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) oxidized cellulose nanofibril (TOCNF) as raw material, the TOCNF was modified by gallic acid (GA) to obtain modified cellulose nanofibril (GA-TOCNF), and the GA-TOCNF was blended with Zein to prepare edible film, and the inhibition zone diameters of E. coli and S. aureus were 11.95 mm and 13.1 mm, respectively.
[0120] As shown in Figure 4 The HA-Zein films prepared by kelp polysaccharide and citrus polyphenol and the HA-Zein films prepared by kelp polysaccharide and Moringa oleifera leaf extract had the maximum inhibition zone diameters of 14.28 mm and 14.75 mm against S. aureus, and the maximum inhibition zone diameters of 12.35 mm and 13.42 mm against E. coli, respectively, which were significantly better than the above-mentioned films.
[0121] 4) Antioxidant activity
[0122] Some researchers prepared Pickering emulsion of cinnamon essential oil by using gallic acid modified Zein, and prepared film by compounding the emulsion with chitosan solution, and the ABTS free radical scavenging rate of the film reached 64.00%. The DPPH and ABTS free radical scavenging activities of the composite film prepared by chitosan / Zein-anthocyanin nanoparticles were 84.05% and 79.17%, respectively. The DPPH free radical scavenging capacity of the composite antibacterial film prepared by Zein / eugenol / IRMOF-3 reached (91.29 ± 1.62)%.
[0123] As shown in Figure 5 The DPPH free radical scavenging activities of the HA-Zein films prepared by kelp polysaccharide and citrus polyphenol and the HA-Zein films prepared by kelp polysaccharide and Moringa oleifera leaf extract were 96.26% and 98.30%, respectively, and the ABTS free radical scavenging activities were 92.34% and 96.72%, respectively, which were significantly better than the above-mentioned films.
[0124] Example 4
[0125] Application of HA-Zein films prepared by kelp polysaccharide and citrus polyphenol and the HA-Zein films prepared by kelp polysaccharide and Moringa oleifera leaf extract in preservation of carp meat
[0126] Fresh live carp was washed with running water, and the surface was dried with filter paper. The gills, internal organs, fish skin, and bones were removed, and the fish was cut into chunks. The HA-Zein film without the addition of functional ingredients was used as a control group. The HA-Zein film containing laminarin and citrus polyphenol and the HA-Zein film containing laminarin and Moringa oleifera leaf extract were coated on the carp chunks. The samples were stored in a refrigerator at -3°C for 20 days. The total volatile basic nitrogen (TVB-N) and the thiobarbituric acid reactive substances (TBARS) were measured during the storage period. Optical tissue sections were prepared and the sample state was observed.
[0127] 1. Total volatile basic nitrogen (TVB-N) determination
[0128] The weighed 15 g of fish meat was added to a 100 mL beaker and homogenized with 75 mL of distilled water. The homogenized sample was added to a distillation tube, shaken to mix the sample solution thoroughly, and soaked for 30 min. A distillation tube without carp meat was used as a blank control tube. Then, magnesium oxide was added to the distillation tube, which was placed in a Kjeldahl nitrogen analyzer. The instrument was operated according to the manufacturer's instructions. After the determination was completed, the sample was titrated with 0.1000 mol / L hydrochloric acid standard titration solution. The titration value was recorded and calculated.
[0129]
[0130] X - the content of volatile basic nitrogen in the sample, in milligrams per hundred grams (mg / 100g)
[0131] V1 - the volume of hydrochloric acid standard titration solution consumed by the test solution, in milliliters (mL)
[0132] V2 - the volume of hydrochloric acid standard titration solution consumed by the reagent blank, in milliliters (mL)
[0133] c - the concentration of the hydrochloric acid standard titration solution, in moles per liter (mol / L)
[0134] 14 - the mass of nitrogen corresponding to 1.0 mL of hydrochloric acid [c(HCl) = 1.000 mol / L] standard titration solution, in grams per mole (g / mol)
[0135] m - the weight of the sample, in grams (g) or the volume of the sample, in milliliters (mL)
[0136] 100 - the conversion factor for the calculation result to milligrams per hundred grams (mg / 100g)
[0137] 2. Thiobarbituric acid reactive substances (TBARS) determination
[0138] Take 5 g fish meat and beat into a paste, then put into a triangular bottle, add 25 mL of trichloroacetic acid with a volume fraction of 7.5%, shake thoroughly in a water bath oscillator at room temperature (37℃) for 30 min, after shaking, filter with double-layer qualitative filter paper into a beaker, discard the precipitate, take 5 mL of supernatant in the filtrate, add 5 mL of 0.02 mol / L TBARS solution into a colorimetric tube with a stopper, adjust the constant-temperature water bath to 100℃, and put the colorimetric tube with the sample into the boiling water, and boil for 40 min. After the boiling water bath is completed, cool at room temperature for 1 h, adjust the low-temperature refrigerated centrifuge to 5500 r / min for 5 min, and put the cooled solution into a 10 mL centrifuge tube for centrifugation. After centrifugation, discard the precipitate, take the supernatant, add 5 mL of chloroform into a colorimetric tube with a stopper, shake well (chloroform should be added dropwise in a fume hood), and after standing and separating, take the supernatant and colorimetric at 532 nm and 600 nm wavelengths under ultraviolet spectrophotometry, and record the absorbance value. Calculate the TBARS value by the formula.
[0139]
[0140] In the formula: A 532nm , A 600nm absorbance at 532 nm and 600 nm wavelengths;
[0141] 3. Preparation and observation of optical tissue section samples
[0142] (1) Sample fixation: cut 1×1×1 cm meat blocks from the control fish meat and the coated fish meat, and immerse in 10% formalin solution for 6 h.
[0143] (2) Dehydration: take out the fixed meat blocks, rinse with water for 12 h, and sequentially immerse the rinsed meat blocks in ethanol solutions with concentrations of 60%, 70%, 80%, and 90% for 1 h each, to dehydrate the sample. Then sequentially immerse the sample in 95% and 100% ethanol solutions for 35 min each, and then immerse the meat blocks in 95% ethanol solution overnight. Finally, take out the overnight sample and immerse in 100% ethanol solution for 30 min until complete dehydration.
[0144] (3) Transparency: first immerse the dehydrated sample in a 1:4 mixture of anhydrous ethanol and xylene for 30 min, and then immerse in a xylene solution for 2 h.
[0145] (4) Wax immersion: immerse the transparent sample in a 2:8 mixture of xylene and paraffin (keep the temperature 2-3℃ higher than the melting point of paraffin, about 60℃) for 30 min, take out the sample and repeat the immersion in pure paraffin for 45 min twice.
[0146] (5) Embedding: Pour the melted wax into the embedding device, mark the number, and quickly pick up the sample block after wax immersion with tweezers and put it into the marked embedding device in turn, so that the sample block tissue is properly arranged and as close to the bottom of the embedding device as possible, and then placed at room temperature for natural solidification or placed in cold water after the paraffin is solidified.
[0147] (6) Slicing: First, cut off the excess paraffin around the sample, and then use a rotary microtome to cut 3-10 μm thick wax sections.
[0148] (7) Mounting: Soak the glass slide in ethanol solution overnight, wipe off the ethanol solution before use, and apply a mixture of protein glycerol, place the wax section on the glass slide, drop a drop of distilled water along the edge, and keep a certain height on the alcohol lamp until the wax section is unfolded, absorb the excess water, and place the glass slide in an oven at 60°C for 2 h.
[0149] (8) Staining: Place the sections in xylene (I) and xylene (II) for 10 min to deparaffinize, then move the deparaffinized sections into a mixture of 1:1 anhydrous ethanol and xylene, and then into 100%, 95%, 80%, 70%, 60% ethanol, and distilled water for 5 min each, place the sections in Harris hematoxylin dye solution for 10 min, rinse the dye with water, place the sections in 1% hydrochloric acid ethanol solution for 30 s. Rinse the sections with water, place the sections in distilled water for 5 min, then place the sections in 60%, 70%, 80%, 95% ethanol for 2 min each, and then place the sections in an ethanol- eosin mixture for 5 min. Finally, place the sections in 90%, 95%, 100% (I), and 100% (II) ethanol solutions for 5 min each, and then dehydrate and clear them in xylene (I) and xylene (II) for 5 min each.
[0150] (9) Mounting and observation: Store the sections with gum for easy observation at any time. Place the stored sections under a digital polarized light microscope and record the internal structure of the sections using software.
[0151] TVB-N is the most commonly used indicator for evaluating fish freshness, indicating the decomposition of proteins in fish due to the action of endogenous enzymes or microorganisms, producing volatile ammonia and amine alkaline compounds. The thiobarbituric acid value is one of the most commonly used methods for determining whether fat is oxidized, especially for evaluating the degree of fat oxidation and spoilage in aquatic products.
[0152] The test results are as follows:
[0153] 1) TVB-N
[0154] There are researchers who use zein / curcumin / kojic acid composite film to preserve chilled chicken, and the total volatile basic nitrogen of the chicken increases by 2 times after 10 days of storage. There are researchers who use tea polyphenol / zein / gelatin coaxial electrospinning film to preserve tuna, and the total volatile basic nitrogen of the tuna increases by 1.43 times and 2.05 times after 9 days and 15 days of storage, respectively. Using leaf aldehyde / zein nanofiber film to preserve tuna, it is found that the total volatile basic nitrogen of the tuna increases by 2.8 times after 10 days of storage.
[0155] As shown in Figure 6 The HA-zein film prepared by kelp polysaccharide and citrus polyphenol and the HA-zein film prepared by kelp polysaccharide and moringa leaf extract for fish storage, the total volatile basic nitrogen of the fish increases by 1.17 times and 1.05 times after 10 days of storage, respectively; the total volatile basic nitrogen increases by 2.05 times and 1.85 times after 20 days of storage, respectively. It is significantly better than the storage application of the above-mentioned films.
[0156] 2) Thiobarbituric acid value (TBARS)
[0157] There are researchers who use zein / curcumin / kojic acid composite film to preserve chilled chicken, and the total volatile basic nitrogen of the chicken increases by 2 times after 10 days of storage. There are researchers who use tea polyphenol / zein / gelatin coaxial electrospinning film to preserve tuna, and the total volatile basic nitrogen of the tuna increases by 1.43 times and 2.05 times after 9 days and 15 days of storage, respectively.
[0158] As shown in Figure 7 The HA-zein film prepared by kelp polysaccharide and citrus polyphenol and the HA-zein film prepared by kelp polysaccharide and moringa leaf extract for fish storage, the total volatile basic nitrogen of the fish increases by 1.17 times and 1.05 times after 10 days of storage, respectively; the total volatile basic nitrogen increases by 2.05 times and 1.85 times after 20 days of storage, respectively. It is significantly better than the storage application of the above-mentioned films.
[0159] 3) Tissue section
[0160] As shown in Figure 8As shown, the muscle fibers of fresh fish meat were complete and regular, the intercellular space was relatively uniform, the muscle fibers and connective tissue were closely arranged, and the connective tissue filled the intercellular space. With the increase of storage time, the ice crystals in the fish meat continuously increased. At 20 d of storage, the generation of ice crystals destroyed the tissue structure of the fish meat, the muscle fibers and muscle septa were severely damaged, and finally led to the muscle fiber deformation. The tissue structure change of the film-treated fish meat samples was delayed. The fish meat samples treated with the laminarin-citrus polyphenol-protein polysaccharide film and the laminarin-moringa leaf extract-protein polysaccharide film had smaller intercellular space between muscle fibers and more uniform distribution of generated ice crystals at 20 d of storage, indicating that the two films had good preservation effect.
[0161] At present, there are few studies on the preservation effect of zein film on fish meat tissue sections, and this study has a certain advancement.
Claims
1. A method for preparing a bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film, characterized in that, The preparation method of the preservative film is as follows: (1) After the hyaluronic acid is completely dissolved in ethanol, zein is added, stirred and dissolved to obtain a zein-hyaluronic acid solution; (2) The citrus polyphenol extract solution is dissolved into the zein-hyaluronic acid solution, and the zein-hyaluronic acid-citrus polyphenol solution is added into distilled water under stirring, and rotary evaporation is carried out in a water bath to remove ethanol; (3) After the laminarin polysaccharide solution and the zein-hyaluronic acid-citrus polyphenol solution from which ethanol is removed are uniformly mixed, glycerol, gelatin and agar are added into the mixed solution, and the mixed solution is stirred and mixed uniformly under water bath condition, defoaming is carried out, film forming is carried out, and after drying, a zein / hyaluronic acid degradable preservative film of laminarin polysaccharide and citrus polyphenol is obtained.
2. The preparation method of the bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film according to claim 1, characterized in that, In step (1), the mass ratio of zein to hyaluronic acid is 5-10:
1.
3. The method for preparing a bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film according to claim 1, characterized in that, In step (2), the mass concentrations of the laminarin polysaccharide solution and the citrus polyphenol solution are 0.75-1.25% and 2.5-5%, respectively.
4. The method for preparing a bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film according to claim 1, characterized in that, After the removal of ethanol in step (2), the content of zein in the mixed solution is 0.2-2%.
5. The method for preparing a bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film according to claim 1, characterized in that, The extraction method of the laminarin polysaccharide is as follows: After the laminarin powder is uniformly mixed with a eutectic solvent by water bath stirring, microwave extraction is carried out, the extract is centrifuged, the supernatant is collected, repeated centrifugation is carried out, the supernatant is collected three times, 95% ethanol is added into the last collected supernatant, mixed, alcohol precipitation is carried out, centrifugation is carried out, the grayish white precipitate is collected, ethanol is volatilized, and freeze-drying is carried out to obtain the laminarin polysaccharide in a loose and porous form without obvious clumping or collapse; The eutectic solvent is a mixture of choline chloride and lactic acid, a mixture of choline chloride and citric acid, a mixture of betaine and lactic acid, or a mixture of betaine and urea.
6. The method for preparing a bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film according to claim 1, characterized in that, The extraction method of the citrus polyphenol is as follows: The citrus dry powder is added with a solvent for immersion and dissolution, mixed, ultrasonic extraction is carried out, centrifugation is carried out, and the supernatant is collected to obtain the citrus polyphenol; The solvent is prepared from choline chloride and glucose in a mass ratio of 1:0.5-2.
7. A method for preparing a bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film, characterized in that, The preparation method of the preservative film is as follows: (1) After the hyaluronic acid is completely dissolved in ethanol, zein is added, stirred and dissolved to obtain a zein-hyaluronic acid solution; (2) The moringa leaf extract is dissolved into the zein-hyaluronic acid solution, and the zein-hyaluronic acid-moringa leaf extract solution is added into distilled water under stirring, and rotary evaporation is carried out in a water bath to remove ethanol; (3) The laminarin polysaccharide solution is taken, and the zein-hyaluronic acid-moringa leaf extract solution from which ethanol is removed is added, and after stirring, the sodium alginate solution, glycerol and sorbitol are added and stirred to obtain a polysaccharide solution; then, Tween-80 is added dropwise, and after homogenization, an emulsion is obtained; defoaming treatment is carried out; (4) The emulsion after defoaming in step (3) is poured into a film, and after drying, a zein-HA film of laminarin polysaccharide and moringa leaf extract is obtained.
8. The method for preparing a bacteriostatic and antioxidant zein / hyaluronic acid degradable preservative film according to claim 7, characterized in that, In step (2), the mass concentrations of the laminarin polysaccharide solution and the moringa leaf extract are 0.75-1.25% and 2.0-3.0%, respectively.
9. The method for preparing a zein / hyaluronic acid biodegradable preservative film with antibacterial and antioxidant properties according to claim 7, characterized in that, The mass concentration of the sodium alginate solution in step (3) is 0.1%; the volume-mass ratio of the corn alcohol-soluble protein-hyaluronic acid-moringa leaf extract solution, the sodium alginate solution, the glycerol and the sorbitol is 50-150 mL: 50-150 mL: 2-3 mL: 1 g.
10. The method for preparing a zein / hyaluronic acid biodegradable preservative film with antibacterial and antioxidant properties according to claim 7, characterized in that, The corn alcohol-soluble protein-hyaluronic acid-moringa leaf extract solution in step (2) is added into distilled water, and the dropping speed is 4-6 mL / min.
Citation Information
Cited By
Antioxidant antibacterial food packaging material based on multi-field synergy and gradient ultrasound and preparation method thereof
CN121930505A
Antioxidant and antibacterial food packaging material based on multi-field synergy and gradient ultrasound and preparation method thereof
CN121930505B